2018
DOI: 10.1371/journal.pbio.2003354
|View full text |Cite
|
Sign up to set email alerts
|

Control of recollection by slow gamma dominating mid-frequency gamma in hippocampus CA1

Abstract: Behavior is used to assess memory and cognitive deficits in animals like Fmr1-null mice that model Fragile X Syndrome, but behavior is a proxy for unknown neural events that define cognitive variables like recollection. We identified an electrophysiological signature of recollection in mouse dorsal Cornu Ammonis 1 (CA1) hippocampus. During a shocked-place avoidance task, slow gamma (SG) (30–50 Hz) dominates mid-frequency gamma (MG) (70–90 Hz) oscillations 2–3 s before successful avoidance, but not failures. Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 85 publications
9
67
2
Order By: Relevance
“…Slow and mid-gamma oscillations could thus be proxies for memory retrieval and encoding ( Carr and Frank, 2012 ), respectively. Such a suggestion is supported by recent work focusing on how gamma oscillations correlate with spatial coding schemes in CA1 ( Bieri et al., 2014 , Cabral et al., 2014 , Dvorak et al., 2018 , Zheng et al., 2016a ). For example, it has been reported that slow (CA3-related) and mid (EC3-related) gamma oscillations bias CA1 spatial coding to a prospective mode (as reflected in animal crossings in which place cells tend to present a maximum instantaneous rate before their “mean” place field center) and to a retrospective mode (i.e., in animal crossings with the place cell maximum instantaneous rate delayed in relation to the mean place field center), respectively ( Bieri et al., 2014 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Slow and mid-gamma oscillations could thus be proxies for memory retrieval and encoding ( Carr and Frank, 2012 ), respectively. Such a suggestion is supported by recent work focusing on how gamma oscillations correlate with spatial coding schemes in CA1 ( Bieri et al., 2014 , Cabral et al., 2014 , Dvorak et al., 2018 , Zheng et al., 2016a ). For example, it has been reported that slow (CA3-related) and mid (EC3-related) gamma oscillations bias CA1 spatial coding to a prospective mode (as reflected in animal crossings in which place cells tend to present a maximum instantaneous rate before their “mean” place field center) and to a retrospective mode (i.e., in animal crossings with the place cell maximum instantaneous rate delayed in relation to the mean place field center), respectively ( Bieri et al., 2014 ).…”
Section: Discussionmentioning
confidence: 65%
“…For example, it has been reported that slow (CA3-related) and mid (EC3-related) gamma oscillations bias CA1 spatial coding to a prospective mode (as reflected in animal crossings in which place cells tend to present a maximum instantaneous rate before their “mean” place field center) and to a retrospective mode (i.e., in animal crossings with the place cell maximum instantaneous rate delayed in relation to the mean place field center), respectively ( Bieri et al., 2014 ). Further, CA1 place cells better represent current spatial position in theta cycles dominated by mid-gamma oscillations ( Dvorak et al., 2018 , Zheng et al., 2016a ). Interestingly, place cell activity in theta cycles with slow gamma oscillations dominating over mid gamma oscillations better represent distant shock zones than the current location in an aversive spatial memory task ( Dvorak et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dis. ; Dvorak et al, 2018, PLoS Biol 1 .) along with electrophysiological correlates of the ability.…”
mentioning
confidence: 99%
“…The following datasets were included in the analysis: 2 CA1 sessions from a teleportation experiment reported in (Jezek et al, 2011), 5 CA1 sessions recorded in the Buzsáki lab (K. Mizuseki et al, n.d.;Kenji Mizuseki, Diba, et al, 2014;Kenji Mizuseki, Sirota, et al, 2009) (specifically session ec14. 215, ec14.277, ec14.333, ec14.260, and ec15.047 from the openly available hc-3 dataset), 16 CA1 sessions from wild-type mice and 16 CA1 sessions from Fmr1-null mice recorded from (Sparks et al, 2017;Talbot et al, 2018;Dvorak et al, 2018), also taken from the openly available hc-16 dataset, 28 CA1 sessions in 3 rats from a remapping experiment reported in (Schlesiger, Cannova, et al, 2015;Schlesiger, Boublil, et al, 2018) and, finally, 178 CA3 sessions from 7 rats in 11 rooms reported in (Alme et al, 2014). Details about the recordings and the experimental settings can be found in the respective references.…”
Section: Resultsmentioning
confidence: 99%